Trade-off between maintenance and protection for multi-state performance sharing systems with transmission loss. (October 2019) - Yi, Kunxiang; Xiao, Hui; Kou, Gang; Peng, Rui
Highlights: The transmission loss during performance sharing is considered. Three different reliability models are proposed. Reliability evaluation algorithms are suggested. The optimal replacement and protection are analyzed. Abstract: In a multi-state system with common bus performance sharing, the performance surplus from one element can be transmitted to other deficient elements as long as the total amount of transmission does not exceed the transmission capacity of the common bus. Existing literature fails to consider the transmission loss during the performance sharing process. Transmission loss widely exists in practice and is affected by many external factors. For example, the power transmission loss is affected by the distance, humility and temperature. In this research, we study a common bus performance sharing system consisting of N independent elements with consideration of performance loss during transmission. We propose three different transmission loss models that are frequently encountered in practice, and suggest their corresponding reliability evaluation algorithms. To improve the system availability, maintenance actions are taken to improve the component reliability, and protection is provided to defend the system against external impacts. We analyze the optimal trade-off between protection and maintenance by minimizing the system cost while satisfying a pre-specified system availability requirement. The proposed reliability models and algorithms are illustrated by a regional power distribution system. The numerical study has demonstrated the importance of considering transmission loss in reliability modeling and optimization.